Urban Atmospherics - Charlton, Ed; Baumann, Hanna; Weintroub, Jill (Writingplace, 2023)
In this article, we consider how an atmospheric attunement to place enables new ways of writing place. Specifically, we draw on fieldwork conducted in Johannesburg and reflect on the outcome of a remote, collective writing process pursued during months of lockdown, when our attention was dominated by talk of air and virality. We think about how our fieldwork provided us with an unsettling preview of the atmospheric anxieties to come, of a time when the very idea of the urban harboured an unseen and largely uncalibrated threat. Having developed a digital StoryMap as a way to host our written reflections, we also assess the importance of our cross-disciplinary method, especially when it comes to sensing and responding to these atmospheric circulations in less anxious, more critical terms.